2022
DOI: 10.1161/circimaging.121.013602
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Composition and Prediction of Incident Atherosclerotic Cardiovascular Disease

Abstract: Background: Whether information on carotid plaque composition contributes to prediction of incident atherosclerotic cardiovascular disease (ASCVD) remains to be investigated. We determined the sex-specific added value of carotid plaque components for predicting incident ASCVD events, beyond traditional cardiovascular risk factors. Methods: Between 2007 and 2012, participants from the population-based Rotterdam Study with asymptomatic caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Increasing evidence indicates that the CP is a characteristic manifestation of progression in atherosclerosis and a powerful predictor of cardiovascular events. 24 Interestingly, our further analysis of the TCR repertoires in the SCA group demonstrated that the patients with EH with CP had significantly lower TCR diversity indexes D50s than those in the patients without CP, despite that there is no significant change in the percentages of dominant TCRβ clones or numbers of big clones, and there were not much changes in V-J gene usages between repertoires of these 2 subgroups either. Taken together, our results indicate that abnormal T-cell responses have a significant effect on SCA in the patients with EH, especially on the formation of CP.…”
Section: Discussionmentioning
confidence: 70%
“…Increasing evidence indicates that the CP is a characteristic manifestation of progression in atherosclerosis and a powerful predictor of cardiovascular events. 24 Interestingly, our further analysis of the TCR repertoires in the SCA group demonstrated that the patients with EH with CP had significantly lower TCR diversity indexes D50s than those in the patients without CP, despite that there is no significant change in the percentages of dominant TCRβ clones or numbers of big clones, and there were not much changes in V-J gene usages between repertoires of these 2 subgroups either. Taken together, our results indicate that abnormal T-cell responses have a significant effect on SCA in the patients with EH, especially on the formation of CP.…”
Section: Discussionmentioning
confidence: 70%
“…From these, 235 were read in full resulting in a final selection of 60 articles. 8–67 Main reasons for exclusion were absence of reporting stratified sex analyses regarding the plaque characteristics (n=89), use of another imaging modality than prespecified (n=24), and no inclusion of a plaque variable of interest (n=24), see Figure 1. Table S2 presents the details of the final included articles.…”
Section: Resultsmentioning
confidence: 99%
“…This idea is supported by the recently published finding that especially in asymptomatic women, IPH increased the risk of atherosclerotic cardiovascular disease (hazard ratio=3.37 [95% CI, 1.81–6.25] for women versus hazard ratio=1.67 [95% CI, 0.98–2.79] for men). 53 Studies on sex-specific risks for (recurrent) stroke risk related to carotid plaque composition are still lacking, probably due to low power, which stresses the importance of the inclusion of an adequate number of both men and women in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel et al demonstrated an association of intraplaque hemorrhage-related unstable carotid plaque features with stroke and myocardial infarction in 1,349 patients without a history of stroke or CAD with subclinical atherosclerosis. This indicates that the presence of intraplaque hemorrhage in the carotid arteries is associated with stroke and CAD development, independent of plaque size or cardiovascular risk factors (74,75).…”
Section: Non-invasive Plaque Imagingmentioning
confidence: 99%